O contexto e a efetividade das pausas intrajornada na saúde dos trabalhadores - Guimarães, Maria Talita dos Santos (2021)
This Master's dissertation is structured in the hybrid format proposed by the Master's and Doctoral Program in Physiotherapy at the Universidade Cidade de São Paulo (UNICID). The document will be presented in three chapters. Chapter 1 presents a brief contextualization about the rest breaks during workdays, called breaks. It presents a brief description of the legislation of breaks in Brazil and in the world. And it describes the terms used to characterize the rest breaks, the protocols used (time, frequency, type of pause). The justification and general objective of this dissertation are also presented. Chapter 2 presents article 1, which is a systematic review, which aimed to discuss the definitions used to characterize rest breaks during workdays. The article will be submitted to the journal Applied Ergonomics Chapter 3 presents study 2, which is also a systematic review, which evaluates the effectiveness of intraday breaks on health, well-being and productivity outcomes. The scientific article will be submitted to the journal Applied Ergonomics. Attached are the registration of systematic reviews in PROSPERO. The annexes present the instruments used for each study design in the methodological quality analyses. And the appendices present the complete results of the methodological quality analysis of the studies included in the systematic reviews.